2016
DOI: 10.2139/ssrn.2555863
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital, Trust, and Firm Performance: The Value of Corporate Social Responsibility during the Financial Crisis

Abstract: During the 2008-2009 financial crisis, firms with high social capital, measured as corporate social responsibility (CSR) intensity, had stock returns that were four to seven percentage points higher than firms with low social capital. High-CSR firms also experienced higher profitability, growth, and sales per employee relative to low-CSR firms, and they raised more debt. This evidence suggests that the trust between the firm and both its stakeholders and investors, built through investments in social capital, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
595
3
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(648 citation statements)
references
References 71 publications
41
595
3
4
Order By: Relevance
“…Their study shown a positive relation between CSR disclosure and financial performance. Lins et al (2017) confirm this theory, showing that during the 2008-2009 financial crisis, firms with high CSR factor, had stock returns that were four to seven percentage points higher than firms with low social capital. In fact this firms firms also experienced higher profitability, growth, and sales per employee relative to low-CSR firms, and they raised more debt.…”
Section: Literature Reviewsupporting
confidence: 61%
“…Their study shown a positive relation between CSR disclosure and financial performance. Lins et al (2017) confirm this theory, showing that during the 2008-2009 financial crisis, firms with high CSR factor, had stock returns that were four to seven percentage points higher than firms with low social capital. In fact this firms firms also experienced higher profitability, growth, and sales per employee relative to low-CSR firms, and they raised more debt.…”
Section: Literature Reviewsupporting
confidence: 61%
“…Corporate sustainability has become one of the mainstream research topics from both a managerial and financial perspective. From a managerial stream of research, several studies highlight the benefits of environmental, social, and governance issues (ESG criteria) on firm value (Fatemi, Glaum, & Kaiser, 2017;Harrison & Wicks, 2013) and financial performance (Friede, Busch, & Bassen, 2015;Lins & Servaes, 2017). Despite the increasing interest in this issue, the effect of environmental, social, and governance issues on overall firm risk by jointly considering debt financing still remains an open, entangling debate (Albuquerque, Durnev, & Koskinen, 2014;Lee & Faff, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, banks and financial institutions exclusively rely on risk sensitivity parameters, and they are still adopting lending practices by estimating risk against the default of borrowers (Zeidan et al, 2015). This evidence leads us to claim that this estimation does not price the potential value the company may be able to set up with social initiatives among all stakeholders and the community, even if the positive impact of the ESG factor on firm value has already been confirmed (Cellier & Chollet, 2016;Fatemi et al, 2017;Gutsche, Schulz, & Gratwohl, 2017;Lins & Servaes, 2017). ESG commitments may serve as risk mitigation on their credit rating in two ways: ESG factors affect borrowers' cash flows and companies' default probability estimation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years corporate social responsibility has become increasingly important both to the consumer and the company [56]. It can affect the way that consumers evaluate a brand and can act as protection for a company in times of crisis [57,58]. Therefore, the encouragement of collaborative work between health researchers, charities and corporations would help to serve both sides.…”
Section: Further Promotional Techniquesmentioning
confidence: 99%